Leukotriene E4 activates human Th2 cells for exaggerated proinflammatory cytokine production in response to prostaglandin D2. - Xue, L; Barrow, A; Fleming, V; Hunter, MG; Ogg, G; Klenerman, P; Pettipher, R (2012)
PGD(2) exerts a number of proinflammatory responses through a high-affinity interaction with chemoattractant receptor-homologous molecule expressed on Th2 cells (CRTH2) and has been detected at high concentrations at sites of allergic inflammation. Because cysteinyl leukotrienes (cysLTs) are also produced during the allergic response, we investigated the possibility that cysLTs may modulate the response of human Th2 cells to PGD(2). PGD(2) induced concentration-dependent Th2 cytokine production in the absence of TCR stimulation. Leukotrienes D(4) and E(4) (LTE(4)) also stimulated the cytokine production but were much less active than PGD(2). However, when combined with PGD(2), cysLTs caused a greater than additive enhancement of the response, with LTE(4) being most effective in activating Th2 cells. LTE(4) enhanced calcium mobilization in response to PGD(2) in Th2 cells without affecting endogenous PGD(2) production or CRTH2 receptor expression. The effect of LTE(4) was inhibited by montelukast but not by the P2Y(12) antagonist methylthioadenosine 5'-monophosphate. The enhancing effect was also evident with endogenous cysLTs produced from immunologically activated mast cells because inhibition of cysLT action by montelukast or cysLT synthesis by MK886, an inhibitor of 5-lipoxygenase-activating protein, reduced the response of Th2 cells to the levels produced by PGD(2) alone. These findings reveal that cysLTs, in particular LTE(4), have a significant proinflammatory impact on T cells and demonstrate their effects on Th2 cells are mediated by a montelukast-sensitive receptor.